The molecular concept of prostate cancer - Koutsilieris, M.; Dimopoulos, M.A.; Doillon, C.; Sourla, A.; Reyes-Moreno, C.; Choki, I. (Cancer Journal, 1996)
This is a brief presentation of the emerging molecular concept of prostate cancer as regards the diagnosis and staging of the disease, analysis of tumour response to hormone-depletion therapy, and the cellular mechanisms that underly progression of the organ-confined tumour toward systemic dissemination and inevitable lethal disease.
Keywords: Diagnosis; hormone therapy; osteoblastic metastasis; Progression; Prostate cancer; Staging